Business diplomacy in practice: challenges in the semiconductor industry’s sustainable supply chain - Krisztina Szegedi; Anh Tuan Tran; Anh Tuan Nguyen (Discover Sustainability)
Abstract The rapid technological evolution, combined with the widespread dissemination of digital devices, has significantly increased the demand for semiconductor chips, highlighting the industry's vital role in globalisation. The semiconductor industry stands at the forefront of technological innovation and economic development, yet it grapples with significant sustainability and supply chain management challenges. Alongside growing sustainability demands within the supply chain, monitoring the semiconductor supply chain faces considerable challenges. Companies typically employ business diplomacy to navigate shifts in the global business environment. By examining the sustainability reports of 19 semiconductor firms selected from the S&P Global Sustainability Yearbook 2024, this research enhances our understanding of how semiconductor companies implement business diplomacy strategies to improve the sustainability of the supply chain by underscoring the critical interrelationship between environmental considerations, social issues, operational efficiency, and strategic international relations with key corporate stakeholders. It also contributes to the theoretical framework of supply chain management and sustainability within the semiconductor industry by illustrating the business diplomacy strategy associated with stakeholder risk management.